Reverse Engineering in the Manufacturing of Lorry Wheels in Palm Oil Processing - Mahmud; Zulfadli; Hamdani; Azwar; Sariyusda (Jurnal Inotera, 2025)
The reverse engineering process in development is widely used to carry out the reverse engineering process for the design of certain products, in this study the reverse engineering process on the palm oil lorry wheel is to improve the design as well as a combination of materials to increase the life of the lorry wheel product in the palm oil processing. The process of scanning the surface of the lorry wheel using camera and the reverse engineering process is carried out by measuring the precision of the lorry wheel by measuring using a precision measuring instrument, data obtained by measurement and reconstruction model. data obtained by measurement and reconstruction model using CAD software and CAE software used to analyze the CAD and CAE software are used to analyze the design results after the reverse engineering process. reverse engineering process. So, it is necessary to develop a reverse engineering system design that will be useful in terms of efficiency and service life of the lorry wheel, in the design of this lorry wheel uses CAD and CAM software to model the lorry wheels with simulation and analysis systems. The next process is to modify and remanufacture the lorry wheel model using machine tools so that the prototype of the manufacturing process can be tested. so that the prototype of the manufacturing process can be tested on the lorry to see the durability of the reverse engineering product. to see the durability of the reverse engineering product. The results of this research showed that the reverse engineering data can be interpolated for further CAE process